The Combination of MBP and BCG-Induced Dendritic Cell Maturation through TLR2/TLR4 Promotes Th1 Activation In Vitro and Vivo - Jiang, LiNa (Mediators Inflamm, 2017)
To explore whether TLR2/TLR4 could be involved in the maturation of dendritic cells and polarization of CD4(+) T cells induced by dendritic cells stimulated with MBP and BCG, in vitro and in vivo experiments using TLR2(−/−) or TLR4(−/−) mice were employed. MBP and BCG elevated CD80, CD86 and MHC class II expressed on dendritic cells and increased IL-12 protein, induced DC maturation, and indirectly promoted Th1 activation. Moreover, MBP and BCG upregulated costimulatory molecules on DCs in a TLR2- and TLR4-dependent manner. The levels of IFN-γ, IL-4, and IL-10 in CD4(+) T cells cocultured with dendritic cells from different types of mice were determined with ELISPOT or ELISA method. TLR2/TLR4 is important in the maturation and activation of dendritic cells and the activation of Th1 cells induced by stimulation with MBP and BCG. In conclusion, TLR2 and TLR4 play an important role in the upregulation of costimulatory molecules and MHC class II molecules on dendritic cells and the activation of Th1 cells induced by stimulation with MBP and BCG. The results above indicate that the combination of MBP and BCG induced the maturation and activation of dendritic cells and promoted Th1 activation via TLR2/TLR4.